Ethanol and its metabolites: update on toxicity, benefits, and focus on immunomodulatory effects. (2nd October 2019) - Le Daré, Brendan; Lagente, Vincent; Gicquel, Thomas
Abstract: This article summarizes recent experimental and epidemiological data on the toxic and beneficial effects of ethanol and its metabolites (acetaldehyde), and focuses on their immunomodulatory effects. The section dealing with the toxic effects of alcohol focuses on its chronic toxicity (liver disorders, carcinogenic effects, cardiovascular disorders, neuropsychic disorders, addiction and withdrawal syndrome, hematologic disorders, reprotoxicity, osteoporosis) although acute toxicity is considered. The role of oxidative metabolism of ethanol by alcohol dehydrogenase, cytochrome P450 2E1, and aldehyde dehydrogenase, as well as the impact of genetic polymorphism in its physiopathology are also highlighted. The section dealing with the beneficial effects of low to moderate alcohol consumption (on cardiovascular system, diabetes, the nervous system and sensory organs, autoimmune diseases, and rheumatology) highlights the importance of anti-inflammatory and immunomodulatory effects in these observations. This knowledge, enriched by a focus on the immunomodulatory effects of ethanol and its metabolites, in particular on the NLRP3 inflammasome pathway, might facilitate the development of treatments that can reduce ethanol's harmful effects or accentuate its beneficial effects.